Solving for n n

Algebra Level 2

Find n n so that:

( 4 n + 7 ) 3 = ( 2 n + 23 ) 4 \large \left(4^{n+7}\right)^3 = \left(2^{n+23}\right)^4


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

( 4 n + 7 ) 3 = ( 2 n + 23 ) 4 ( 2 2 n + 14 ) 3 = ( 2 n + 23 ) 4 2 6 n + 42 = 2 4 n + 92 6 n + 42 = 4 n + 92 2 n = 50 n = 25 \large \begin{aligned} \left(4^{n+7}\right)^3 & = \left(2^{n+23}\right)^4 \\ \left(2^{2n+14}\right)^3 & = \left(2^{n+23}\right)^4 \\ 2^{6n+42} & = 2^{4n+92} \\ \implies 6n+42 & = 4n + 92 \\ 2n & = 50 \\ \implies n & = \boxed{25} \end{aligned}

Thank you.

Hana Wehbi - 3 years, 8 months ago

( 4 n + 7 ) 3 = ( 2 n + 23 ) 4 \large{\left(4^{n+7}\right)^3=\left(2^{n+23}\right)^4}

From the power rule , ( a n ) m = a n × m (a^n)^m=a^{n \times m} , so we have

4 3 ( n + 7 ) = 2 4 ( n + 23 ) \large{4^{3(n+7)}=2^{4(n+23)}}

2 2 ( 3 ) ( n + 7 ) = 2 4 ( n + 23 ) \large{2^{2(3)(n+7)}=2^{4(n+23)}}

2 ( 3 ) ( n + 7 ) = 4 ( n + 23 ) \large{2(3)(n+7)=4(n+23)}

6 n + 42 = 4 n + 92 \large{6n+42=4n+92}

2 n = 92 42 \large{2n=92-42}

n = 25 \color{plum}\boxed{\large{n=25}}

Thank you.

Hana Wehbi - 3 years, 8 months ago

Thank you keep posting solutions

Sahil Kumar - 3 years, 7 months ago

Log in to reply

Thank you keep posting solutions

Sahil Kumar - 3 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...